A framework for a development of an intelligent CNC controller based ON step-NC - Daud, Mohd Elias; Yusof, Yusri; Minhat, Mohamad (2011)
STEP-NC standard contains information on how CNC machine tools can be represented from STEP product data model. STEP-NC is an extension of STEP which is the standard for exchange product model data. This determines the neutral data format for digital information from a product. This paper is to propose an architecture of intelligent controller via multi-agent-based conceptual as the reference architecture. It can be successfully used to create an open CNC on ISO standard of ISO 14649 and ISO 10303. This offers interoperability, portability, and adaptability. The proposed framework consists of four main modules, STEP-NC interface, simulator, data warehouse, and communication. In order to optimize, the controller should incorporate with various technology related to intelligent, such as kernel software, open communication port and open hardware design. The architecture will be implemented in CNC controller and to be tested later on actual milling machine. It will simplify the design of CNC machine controller with the architecture layers responsible for data processing, data storage, execution and feedback. This paper will discuss order towards the requirements for global interoperable manufacturing for real-life machining system.